The fishermen’s associations of the Basque Country. Changes and historical and current influences in inshore fishing: Case study of Santurtzi (Biscay) - Rubio Ardanaz, Juan Antonio (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2020)
The fishermen's associations of the Basque Country have been responsible for bringing together, adapting and giving continuity to the profession, depending on the social, economic and technological changes of each historical moment. Inshore fishing has found in these institutions the way to face the vicissitudes of this fishing modality in a process of continuous changes. The traditional model will change definitively entering a period of modernization, finally converging in the current forms of production dependent on the current capitalist model. To understand the different phases of this situation we have studied the case of the fishermen's association of Santurtzi (Bizcay).